RECOMMENDATION ON THE 7-VALENT PNEUMOCOCCAL CONJUGATED VACCINE AMONG CHILDREN - M.V. Fedoseenko; A.A. Stepanov (Union of pediatricians of Russia, 2009)
The article provides a guideline and practical recommendations of the Advisory Committee on Immunization Practices for the use of the 7'valent conjugated pneumococcal vaccine.Key words: pneumococcal infection, vaccination, children.